Faktor Risiko Dermatitis Kontak Akibat Kerja Pada Para Pekerja Salon Di Kelurahan Padang Bulan Sumatera Utara Tahun 2017 - Fadlan Aufar Malik; Irma Damayanti Roesyanto (Jurnal Kesehatan Indonesia, 2018)
Skin disease is the most occupational disease after bone and muscle. Occupational Contact dermatitis is in the first rank in occupational skin disease, 80% is irritant contact dermatitis and the remaining 20% is allergic contact dermatitis who have the highest incidence of contact dermatitis were salon workers. Generally, this study aims to determine the risk factors of occupational contact dermatitis on salon workers.This study is analytic method study which uses cross sectional design, where the data is only taken once in a time by using primary data from interview and questionnaire instrument as a tool and respondent were drawn using consequtive sampling. The study showed that 47,3% of salon workers had contact dermatitis. Risk factors which have a significant relationship with contact dermatitis are chemical exposure frequency (p value = 0,020) and duration of water exposure (p value = 0,005). The result of multivariate analysis showed that the most dominant variable causes occupational contact dermatitis was the duration of skin exposure (p value = 0,030; OR = 3,783). Frequency of exposure and duration of exposure have a significant relationship with occupational contact dermatitis to the salon workers in Kelurahan Padang Bulan. Meanwhile, sex, age, long of work and use of personal protective equipment have no significant relationship with occupational contact dermatitis to the salon workers in Kelurahan Padang Bulan.